Trucks Night and Day - Relf, Patricia; Nang ChanYeema (New York, USA Scholastic Inc., 2000)
In brief text and pictures, presents a variety of trucks working in different settings, including farms, highways, airports, ski resort, and more.
Keywords: Juvenile Nonfiction